Tantangan dan Upaya Penguatan Perlindungan Data Pribadi Nasabah dalam Layanan Perbankan dan Dompet Digital - Wahyu Wulandari; Dina Gita Prianti; Elyssa Alya Nasution; Zefanya Gusti Najwa; Amanda Cahya Maulita; Baidhowi . (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The development of information technology has driven significant transformation in the financial sector through the presence of digital banking services and electronic wallets (e-wallets). Although these innovations improve efficiency and financial inclusion, the use of personal data in their operations poses serious risks such as misuse, illegal access, and data breaches that can harm customers. This study aims to analyze the regulation of personal data protection in Indonesia, the forms of responsibility of service providers, as well as the obstacles and efforts to strengthen its protection. The research method used is normative juridical with a legislative and comparative approach. The discussion results show that although regulations such as the Personal Data Protection Law (UU PDP) and Financial Services Authority Regulations (POJK) exist, personal data protection still faces challenges, including low digital literacy among the public, cyberattack risks, system security weaknesses, and insufficient supervision. Efforts to strengthen protection need to be carried out through massive public education, implementation of global security standards (Security by Design), strict law enforcement, and cross-sector collaboration to create a safe and trusted digital financial ecosystem.